2018
DOI: 10.1002/humu.23418
|View full text |Cite
|
Sign up to set email alerts
|

Tricho-Hepato-Enteric Syndrome mutation update: Mutations spectrum ofTTC37andSKIV2L, clinical analysis and future prospects

Abstract: Tricho-Hepato-Enteric syndrome (THES) is a very rare autosomal recessive syndromic enteropathy caused by mutations of either TTC37 or SKIV2L genes. Very little is known of these two gene products in mammals nor of the pathophysiology of the disease. Since the identification of the genes, we have set up the molecular diagnostic of THES in routine, gathering a large cohort with clinical and molecular data. Here, we report the phenotype and genotype analysis of this cohort together with an extensive literature re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 42 publications
1
63
2
Order By: Relevance
“…In this study, we performed WES on a selected subgroup of CVID patients with a classical infectious phenotype combined with autoimmunity, inflammation, and/or malignancy and identified probable and possible disease-causing candidate gene variants through a targeted bioinformatics analysis, focusing on 564 primary immunodeficiency-related genes. This approach resulted in the identification of two previously described gene variants in NFKB1 (21,32), nine novel variants, including variants in STAT3, TNFAIP3, IL-17F, IRAK4, TTC37, DDX41, NLRC3, TNFRSF1A, and PLCG2 (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(34)(35)(36) associated with different states of immune dysregulation but not previously associated with CVID, and with possible probable diseasecausing impact according to bioinformatics. Altogether, we identified probable/possible disease-causing variants in nine of 20 patients in this CVID subpopulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we performed WES on a selected subgroup of CVID patients with a classical infectious phenotype combined with autoimmunity, inflammation, and/or malignancy and identified probable and possible disease-causing candidate gene variants through a targeted bioinformatics analysis, focusing on 564 primary immunodeficiency-related genes. This approach resulted in the identification of two previously described gene variants in NFKB1 (21,32), nine novel variants, including variants in STAT3, TNFAIP3, IL-17F, IRAK4, TTC37, DDX41, NLRC3, TNFRSF1A, and PLCG2 (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(34)(35)(36) associated with different states of immune dysregulation but not previously associated with CVID, and with possible probable diseasecausing impact according to bioinformatics. Altogether, we identified probable/possible disease-causing variants in nine of 20 patients in this CVID subpopulation.…”
Section: Discussionmentioning
confidence: 99%
“…A novel likely deleterious frameshift S1330fs * 14 variant in tetratricopeptide repeat domain (TTC)37 was found in P15 (Tables 2, 3). Her symptoms were only slightly overlapping with autosomal recessive Tricho-Hepato-Enteric Syndrome (OMIM #222470), which is characterized by intrauterine growth retardation, wooly hair, facial dysmorphism, intractable diarrhea in infancy, and immunodepression, previously associated with mutations in this gene (27). However, some patients have been described with only one mutation, and therefore a weak phenotype might be caused by a heterozygous variant.…”
Section: Identified Variantsmentioning
confidence: 97%
“…Then, they examined the lab diagnostic cohort in detail for clinical manifestations. They stated that “for the first time, we are able to suggest that patients lacking SKIV2L seem more severely affected than those lacking TTC37, in terms of liver damage and prenatal growth impairment.” 16 …”
Section: Discussionmentioning
confidence: 99%
“…Further analyses revealed that most THES patients had defects in the immune system with low levels of switched immunoglobulins, highly variable responses to vaccination including unresponsiveness of specific antigens, impaired T cell and NK cell functions such as low production of γ-interferon and abnormal T cell proliferation, and severe Epstein Barr Virus (EBV) infection [77]. It appears that 60% of the THES patients had a genetic deficiency of TTC37 [59] and 40% had a deficiency of SKIV2L [78], and many of those homozygous deficiencies were the results of consanguineous marriage. Since the discovery of THES, a spectrum of disease phenotypes and severity has emerged, and the disease has been reported in multiple racial groups [74,75,79,80,81].…”
Section: Skiv2l or Ski2wmentioning
confidence: 99%
“…Since the discovery of THES, a spectrum of disease phenotypes and severity has emerged, and the disease has been reported in multiple racial groups [74,75,79,80,81]. It has been noticed that THES patients with deficiencies of SKIV2L experienced more severe disease in terms of liver damage and impairment of prenatal growth than those with deficiencies of TTC37 [78]. THES patients with deficiency of Skiv2l but not deficiency of TTC37 exhibited a remarkable type I interferon stimulated gene expression profile [56].…”
Section: Skiv2l or Ski2wmentioning
confidence: 99%